IDENTIFIKASI MEDICATION ERROR PADA RESEP PASIEN PEDIATRI di PALU INDONESIA - Firdayanti Firdayanti; Amelia Rumi (As-Syifaa Jurnal Farmasi, 2020)
Medication error is an event that is detrimental to the patient and can also endanger the safety of the patient, occurring as long as the patient is in a preventable health care workforce. This research aims to determine the form and percentage of medication error on prescription pediatric patients aged 2 months – 18 years in one of the hospitals in the city of Palu, Indoenesia. This research is a descriptive cross-sectional research with data retrieval conducted prospectively with the total sampling method. The sample of this study has 118 prescription paediatric patients in the period of September to October 2019. With the results of the research medication error in the prescribing  phase ie no SIP doctor 92.37%, no high patients 92.37%, no weight 90.67%, no age of the patient 72.88%, no medical record number 64.40%, no dosage form 58.47. Phase of transcribing error is no patient status 81.65%, no age of the patient 72.88%, no apparent medical record number 59.32%, not clear the dosage form of 53.38%. The dispensing error is a 61.86% incorrect or incomplete tag. The administration error phase of the patient is not given an explanation about the cure 66.10%%, it can be concluded that it has been medication error in one of the hospitals in the city of Palu, Indonesia